Increasing the Learning Result and Student Activity on Virus Concept through Problem Based Learning - Rusmalina Rusmalina; Aminuddin P. Putra (Universitas Sebelas Maret, 2015)
Research to learning outcome and student's activity done to X MIA class student 3 SMAN 5 Banjarmasin in virus concept. This research aim to describe result increase learn and student's activity in X MIA class 3 SMAN 5 Banjarmasin by using Problem Based Learning. Research methods was class action research (PTK) which involved 39 students consisted from 12 fellow and 27 women as research subject. Research result indicate that model (PBM)'s used in Virus material can improve result learn represent postes result in I cycle totalled 41,5 % and II cycle totalled 86 %, from data obtained show classical mastery accessibility that determined as big as ≥ 85 %. Student's activity increase seen in I cycle to II cycle in problem solving seen from data obtained in I cycle totalled 94 % and in II cycle totalled 98 %. LKS result indicates increase in I cycle 77,68 % and II cycle totalled 87,93 %. Process evaluation and psychomotor appertain well. Behavior assessment character and social craftsmanship appertain satisfy. Product assessment result show increase with I cycle percentage value and II namely 3,01 % and 3,72 %. Based on student's response data in Problem Based Learning states 61,38 % agrees, until learning use PBM model summed can improve learning outcome and X MIA class student's activity 3 SMAN 5 Banjarmasin in Virus concept.Keywords: Virus Concept, PBM, learning outcomes and student activity